Радикальные алгебры, подгруппы присоединенных групп которых являются подалгебрами - Попович, С.В.; Сысак, Я.П. (Український математичний журнал, 1997)
Отримана характеризація радикальних алгебр, підгрупи приєднаних груп яких є підалгебрами. Доведено, зокрема, що такі алгебри нільпотентиі з індексом нільпотентності, який не перевищує 3. Дана повна класифікація тих із них, що породжені двома елементами. We obtain the characteristic for radical algebras subgroups of whose adjoint groups are subalgebras. In particular, we prove that the algebras of this sort are nilpotent with nilpotent length at most three. We give the complete classification of those algebras under consideration which are generated by two elements.